Growth Performance, Blood Profile, and Carcass Characteristics of Weaned Pigs Fed Low Crude Protein Diets Supplemented with Lysine - T. K. Ojediran; E. O. Babatunde; S. O. Olokun; O. K. Adigun; B. B. Ajao; F. Emaye; M. D. Shittu; F. A. Adejoro (Faculty of Animal Science, Bogor Agricultural University, 2021)
Supplementing low crude protein (CP) diets for pigs with exogenous amino acid may help improve growth performance, minimize the environmental impact associated with nitrogen loss and improve the sustainability of pork production. A total number of thirty (30) Large white x Landrace weaned pigs between the age of 8-10 weeks and an average weight of 11.5 ± 0.39 kg were used to evaluate the effect of lysine supplementation of a low CP diet on growth performance, blood profile, and carcass characteristics of weaner piglets. Weaned pigs were acclimatized for seven days, randomly allotted to five (5) dietary treatments with six weaners per treatment and fed a weaner diet based on maize-soybean while wheat bran and dried cassava peel were added to balance the diet nutrients. The animals were allocated to either a control diet containing 22.6% CP or a diet with 2.5%, 5.0%, 7.5%, and 10% reduction in diet CP. Each animal consumed the respective diet for six weeks during which growth performance was monitored. Afterward, 5 mL of blood was sampled for analysis, and all the pigs were slaughtered for carcass analysis. Average daily gain, total weight gain, and average daily intake were not significantly different across the groups (p>0.05). While feed cost per kg was lower with the 7.5% and 10% diet CP reduction (p<0.05), feed cost per weight gain was not different across the animals. Most haematological and serum biochemical variables were not affected by CP reduction, while carcass weight was equally not affected by diet CP (p>0.05). However, the abdominal fat percentage of carcass reduced slightly with the reduced diet CP. Therefore, up to 10% reduction in diet CP from 22.6%, with 0.1% lysine supplementation, had no negative impact on growth without compromising the immunity indicators of weaned pigs. Furthermore, there was no negative consequence on carcass characteristics and the primal cuts.